2015
DOI: 10.1161/circulationaha.114.013947
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation in the United Kingdom

Abstract: Background-We assessed trends in the performance of transcatheter aortic valve implantation in the United Kingdom from the first case in 2007 to the end of 2012. We analyzed changes in case mix, complications, outcomes to 6 years, and predictors of mortality. Methods and Results-Annual cohorts were examined. Mortality outcomes were analyzed in the 92% of patients from England and Wales for whom independent mortality tracking was available. A total of 3980 transcatheter aortic valve implantation procedures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
59
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(71 citation statements)
references
References 33 publications
10
59
2
Order By: Relevance
“…(12,34,43,44) Chronic kidney disease is associated with increased mortality after TAVR and surgical AVR. (33,45,46) End-stage renal disease is less common but occurs in 2% of surgical AVRs and up to 4% of patients in the U.S. TAVR registry, where it is associated with a 66% increase in the hazard of 1-year mortality. (34,46) Acute kidney injury after valve replacement is also associated with increased mortality and may occur less commonly after TAVR compared to surgical AVR.…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…(12,34,43,44) Chronic kidney disease is associated with increased mortality after TAVR and surgical AVR. (33,45,46) End-stage renal disease is less common but occurs in 2% of surgical AVRs and up to 4% of patients in the U.S. TAVR registry, where it is associated with a 66% increase in the hazard of 1-year mortality. (34,46) Acute kidney injury after valve replacement is also associated with increased mortality and may occur less commonly after TAVR compared to surgical AVR.…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…(13,14,46,52) Many studies have demonstrated that diabetes is associated with increased mortality after surgical AVR or TAVR. (33,53,54) According to a post-hoc analysis of PARTNER trial patients, there was a survival benefit, no increase in stroke, and less renal failure in diabetic patients treated with TAVR compared to surgical AVR. (52) However, this survival benefit with TAVR among diabetic patients was not observed in the CoreValve sub-group analysis.…”
Section: Medical Comorbiditiesmentioning
confidence: 99%
“…26 In the UK TAVI registry, periprocedural stroke was shown as the strongest independent procedural predictor of long-term mortality (hazard ratio, 3.00; P<0.0001). 13 In Placement of Aortic Transcatheter Valves (PARTNER) 1 trial, 25 periprocedural stroke was associated with ≈2-to 6-fold increase in hospital mortality, a 3-to 12-fold increase in mortality at 30-day, and a 2-to 16-fold increase in longterm mortality. 26 However, although periprocedural stroke or transient ischemic attack was more common after TAVI than after SAVR at 30 days (5.5% versus 2.4%; P=0.04), this difference gradually decreased and by 5 years, the difference had dissipated (TAVI, 14.7% versus SAVR, 15.9%).…”
Section: Cerebral Embolismmentioning
confidence: 99%
“…Length of in-hospital stay remained unchanged for SAVR, but decreased for TAVI over time. 12 Baseline overall risk remains an important predictor of 30-day mortality 13 and showed, in many studies, a gradual reduction in patients considered for TAVI. 8,14,15 In some series, more than one third of patients routinely treated with TAVI had an intermediate-to-low risk (defined as a Society of Thoracic Surgeons-predicted risk of operative mortality [STS-PROM] ≤8).…”
mentioning
confidence: 99%
See 1 more Smart Citation